What can we learn from in vivo biomechanical investigations of lower extremity? - Lamontagne, M.; Benoit, D. L.; Ramsey, O. K.; Caraffa, A.; Cerulli, G. (ISBS - Conference Proceedings Archive (Konstanz), 2005)
In vivo biomechanical investigations of human movement are needed to better understand function and injury mechanism of the musculoskeletal system and to validate models or methods that otherwise could not be validated. In this report, we showcase two biomechanical approaches that use in vivo experiments to directly measure skin movement artefacts and the role of hamstring neuromuscular control in protecting the anterior cruciate ligament (ACL). The study on skin movement artefacts revealed that surface markers provided kinematics which can present repeatable patterns within a participant for various movements. However these repeatable patterns must not be misinterpreted as accurately representing skeletal kinematics, at least beyond the sagittal plane of movement. In the second investigation the neuromuscular control of the hamstring and gastrocnemius muscles showed a protective mechanism to prevent excessive ACL elongation, whereas the quadriceps muscles resisted against the collapsing of the knee joint after foot impact with the ground. This paper highlights the value of in vivo experimentation in contributing to our understanding of biomechanical functions or processes.